Effects of Different Feeding Frequencies on Broiler Chickens’ Growth Performance and Intestinal Villus Development - Chaiyasing, Rattanatrai; Srinontong, Piyarat; Aengwanich, Worapol; Promsatit, Satitpong; Cahyadi, Danang Dwi; Wandee, Jaroon (Trends in Sciences, 2024)
This experiment was conducted to determine the effects of feeding frequency on growth performance and development of small intestine in broiler chickens from 1 to 14 days of age. Forty Aber acres broiler chicks at 1 day old were randomly assigned to 4 treatments as follows - T1: feeding once daily (100 % diet at 6:30), T2: feeding twice daily (50 % diet at 6:30 and 18:30), T3: feeding 4 times per day (25 % diet at 6:30, 11:30, 16:30 and 21:30) and T4: feeding 6 times per day (16.67 % diet at 6:30, 9:30, 12:30, 15:30, 18:30 and 21:30). Chickens were fed with commercial broiler rations for 14 days. Growth performance parameters including BW, BW gain, FI and FCR were determined. Changes in intestinal villus morphology were examined by hematoxylin and eosin (H&E) dye staining. Results showed that chickens fed 4 and 6 times per day had lower (p < 0.05) BW, BW gain and FI when compared with chickens fed once daily, from 1 to 7 days of age. However, at 14 days of age, there were no significant differences in all parameters of growth performance. There were no changes in gross anatomy of the small intestine. Fixed feeding 4 and 6 times per day resulted in the villus height of the jejunum and ileum being higher (p < 0.05) than when feeding once a day. Feeding 6 times per day resulted in the highest villus density in jejunum among feed regimes. The results suggested that both once and multiple daily feedings were suitable approaches to achieve optimum growth performance for broiler chickens from 1 to 14 days of age. Fixed feeding 6 times per day being the most beneficial for improving intestinal villus development. HIGHLIGHTS Feeding frequency is one of feed restriction method in broilers management From 1 to 7 days of age feeding fed 4 and 6 times per day show lower growth performance than feeding once daily, but not for 14 days of age Fixed feeding 4 and 6 times per day present the villus height at jejunum and ileum higher than feeding once daily Fixed feeding 6 times per day is the most effective solution for enhancing intestinal villus development Here, the experiment demonstrates for the first time that the compensatory growth effects by frequently feeding is at least mediated through adaptation of villus morphology in the small intestine along with improved feed consumption GRAPHICAL ABSTRACT